Gene-edited Mtsoc1 triple mutant Medicago plants do not flower - Poulet, Axel; Zhao, Min; Peng, Yongyan; Tham, FangFei; Jaudal, Mauren; Zhang, Lulu; van Wolfswinkel, Josien C.; Putterill, Joanna (Frontiers in Plant Science, 2024)
Optimised flowering time is an important trait ensuring successful plant adaptation and crop productivity. SOC1-like genes encode MADS transcription factors known to play important roles in flowering control in many plants. This includes the best characterised eudicot model Arabidopsis thaliana (Arabidopsis) where SOC1 promotes flowering and functions as a floral integrator gene integrating signals from different flowering time regulatory pathways. Medicago truncatula (Medicago) is a temperate reference legume with strong genomic and genetic resources used to study flowering pathways in legumes. Interestingly, despite responding to the similar floral-inductive cues of extended cold (vernalisation) followed by warm long days (VLD), as winter annual Arabidopsis, Medicago lacks FLC and CO which are key regulators of flowering in Arabidopsis. Unlike Arabidopsis with one SOC1 gene, multiple gene duplication events have given rise to three MtSOC1 paralogs within the Medicago genus in legumes; one Fabaceae group A SOC1 gene, MtSOC1a, and two tandemly-repeated Fabaceae group B SOC1 genes, MtSOC1b and MtSOC1c. Previously, we showed that MtSOC1a has unique functions in floral promotion in Medicago. The Mtsoc1a Tnt1 retroelement insertion single mutant showed moderately delayed flowering in long and short day photoperiods, with and without prior vernalization, compared with wild type. On the other hand, Mtsoc1b Tnt1 single mutants did not have altered flowering time or flower development, indicating that it was redundant in an otherwise wild type background. Here, we describe the generation of Mtsoc1a Mtsoc1b Mtsoc1c triple mutant lines by CRISPR-Cas9 gene editing. We studied two independent triple mutant lines that segregated plants that did not flower and were bushy in floral inductive VLD. Genotyping indicated that these non-flowering plants were homozygous for predicted strong mutant alleles of all three MtSOC1 genes. Gene expression analyses by RNA-seq and RT-qPCR indicate that these plants remain vegetative. Thus overall, the non-flowering triple mutants are dramatically different from the single Mtsoc1a mutant and the Arabidopsis soc1 mutant; implicating multiple MtSOC1 genes in critical overlapping roles in the transition to flowering in Medicago.